BUDAYA PESANTREN SALAFI (STUDI KETAHANAN PESANTREN SALAFI DI PROVINSI BANTEN) - Hanafi, M. Syadeli (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2018)
Salafi pesantren is a conventional Islamic educational institution which rooted deeply at Muslim society in Indonesia, especially in Banten Province. Its ability to keep existing and competing with modern pesantren is extraordinary, even though challenges and obstacles coming from competition with both modern pesantren and public schools are very hard, not to mention a stigma given to it directly or indirectly as a place to train radical and militan Islam, has trully destroyed salafi pesantren‟s popularity in society. This research intended to disclose the essential values of salafi pesantren‟s organizational culture along with its influence on its own existence in the society. Research result found out that organizational culture such as value, conviction, custom, and life philosophy is built and maintained by kiai (Islamic scholar, usually also a head of pesantren) as a central figure. Manifestation of pesantren‟s culture includes cultural kinship, solidarity and helpfulness, quality, honesty, and responsibility. These cultures remain sustainable due to the existence of cultural adhesive which are: obedience, familiarity, honesty, and santri‟s (students of pesantren or madrasah) responsibility towards kiai that interpreted as an act of tawaddu‟ (humility), observance, and sincerity.